Korelasi Kompetensi dan Kinerja Perekam Medis dan Informasi Kesehatan di Puskesmas Kabupaten Cirebon - Indriartanti, Dian Rizki; Subianto, Totok; Suhartini, Suhartini; Elfi, Elfi (Indonesian of Health Information Management Journal (INOHIM), 2025)
AbstractCompetence is a person's ability to carry out tasks and responsibilities in a work environment that includes knowledge and skills in improving professional performance standards. The performance of employees is determined by their level of motivation and competence to achieve good work results. The study aims to determine the relationship between competence and performance of medical records and health information officers in Cirebon district. The population in this study were 60 medical record officers in Cirebon district. The sample taken was 44 PMIK officers with a medical record and health information education background who worked at the health center. This research uses a type of observational quantitative method and research design using a cross-sectional approach. The results of the univariate analysis showed that the characteristics of the dominant age respondents were ≤ 25 years by 65.9%, the most tenure was < 2 years by 56.8%. Then, the competence of medical record officers in the competent category was 50% of respondents and the performance of medical record officers in the good category was 54.5% of respondents. Analysis bivariate using the chi-square test which obtained a P-value of 0.762> 0.05, meaning that there is no correlation between the competence and performance of medical recorders and health information at the Cirebon district health center.Keyword: Competency, Performance, Medical Records, Health Center. AbstrakKompetensi merupakan kemampuan seseorang untuk melaksanakan tugas dan tanggung jawab di lingkungan kerja yang mencakup pengetahuan dan keterampilan dalam meningkatkan standar kinerja professional. Kinerja karyawan ditentukan oleh tingkat motivasi dan kompetensi mereka untuk mencapai hasil kerja yang baik. Penelitian ini bertujuan mengetahui hubungan antara kompetensi dengan kinerja petugas rekam medis dan informasi kesehatan di kabupaten Cirebon. Populasi dalam penelitian ini sebanyak 60 orang petugas rekam medis di kabupaten Cirebon. Sampel yang diambil yaitu 44 orang petugas PMIK berlatar pendidikan rekam medis dan informasi kesehatan yang bekerja di puskesmas. Penelitian ini mempergunakan jenis metode kuantitatif observasional dan desain penelitian menggunakan pendekatan cross sectional. Hasil penelitian Analisis univariat menunjukkan karakteristik responden umur dominan adalah ≤ 25 tahun sebesar 65.9%, masa kerja paling banyak adalah < 2 tahun sebanyak 56.8%. Kemudian, kompetensi petugas rekam medis dengan kategori kompeten sebesar 50% responden dan kinerja petugas rekam medis dengan kategori baik sebesar 54.5% responden. Analisis bivariat menggunakan uji chi-square yang memperoleh hasil P-value 0.762 > 0,05 artinya tidak ada korelasi antara kompetensi dan kinerja perekam medis dan informasi kesehatan di puskesmas kabupaten Cirebon.Kata Kunci: kompetensi, kinerja, rekam medis, puskesmas